Energy Storage and Geographical Distribution of Wind Power to Improve Frequency Stability - Pandit D.; Bera A.; Saket R.K.; Mitra J.; Nguyen N. (My University, 2025)
Penetration of wind energy has increased significantly in the power grid in recent times. Although wind is abundant, environment-friendly, and cheap, it is variable in nature and does not contribute to system inertia as much as conventional synchronous generators. These negative characteristics of wind lead to concerns over the frequency stability of power systems. This paper proposes a planning strategy to improve grid frequency stability by jointly deploying energy storage systems (ESSs) and geographical distribution of wind power. ESSs can provide inertial support to the grid by rapidly injecting active power into the system. At the same time, geographical separation/distribution of wind power can reduce wind power output variability and improve the inertia contribution from wind farms. The ESSs are sized based on the balance inertia needed for frequency stability, obtained using an analytical method and a mixed timing Monte Carlo simulation (MCS) based framework. The effect of the distribution of wind power across geographical regions is incorporated into the framework to study possible reductions in the ESS size while maintaining the system frequency stability. The proposed strategy is implemented on the modified WSCC 9-bus system. © 2023 IEEE.